Oḍiā sāhityaku Ākāśabāṇīra dāna - Mahānti, Brajamohana (Oḍiśā Buk Ṣṭora, 1986)
Study of the role of broadcasting in the development of Oriya literature in India
In Oriya. - Includes bibliographical references (p. [665]-712)
Keywords: Oriya literature; Radio broadcasting; Television broadcasting